1996
DOI: 10.1111/j.1600-0420.1996.tb00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical urea as a treatment for non‐infectious keratopathy

Abstract: The purpose of this study was to evaluate topical urea ophthalmic ointment as an agent to promote epithelial healing. Corneal epitheliopathy and epithelial defects were chemically induced in rabbits. Urea ophthalmic ointment was administered to one eye and control ointment to the fellow eye. The rabbits were examined by a masked observer for eleven days and points were awarded for steps of improvement in their ocular surface disease. The eyes receiving the urea ointment improved an average of 5.73 points while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Indeed, urea is widely and safely used in pharmaceutical and cosmetic formulations because it is keratolytic and moisturizing, and thus it enhances cellular regeneration and repair. Urea is useful to treat different diseases, such as dry skin, damaged cutaneous annexes, non-infectious keratopathy, and injured corneal epithelium [19,20,21]. Hence, HA-CL could be a promising biomaterial for topical treatments requiring simultaneous re-epithelialization and hydration for the resolution of aesthetic/functional skin and mucosae problems [9,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, urea is widely and safely used in pharmaceutical and cosmetic formulations because it is keratolytic and moisturizing, and thus it enhances cellular regeneration and repair. Urea is useful to treat different diseases, such as dry skin, damaged cutaneous annexes, non-infectious keratopathy, and injured corneal epithelium [19,20,21]. Hence, HA-CL could be a promising biomaterial for topical treatments requiring simultaneous re-epithelialization and hydration for the resolution of aesthetic/functional skin and mucosae problems [9,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, urea is currently used safely and effectively in large populations of patients across a wide variety of disease settings, such as dry and scaly skin (ichthyosis, xerosis, psoriasis, corns, calluses), damaged cutaneous annexes (ingrown, devitalized nails), noninfectious keratopathy, and injured corneal epithelium. 52,53 Urea pharmaceutical and cosmetic treatments are generally well tolerated and associated with few mild and transient side effects, without systemic toxicity. Therefore, clinicians and health care providers continue to consider urea as a viable treatment option for patients.…”
Section: Future Perspectives: Dermal Fillers Based On Hyaluronic Acidmentioning
confidence: 99%
“…Tear supplementation is the treatment of choice to control signs and symptoms of dry eye syndrome [ 1 ], and HA artificial tears eye drops are and among the most studied [ 4 , 10 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 29 , 30 ]. Corneal re-epithelialization, recovery and maintenance of ocular epithelium physiological conditions can be promoted also by urea therapy [ 32 ]. Hence, the novel hyaluronan derivative cross-linked with urea could be a valid therapy for KCS.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, urea is well known to be a moisturizing agent, thanks to its ability of water retention, which promotes cellular regeneration and reparation [ 21 ]. Charlton et al [ 32 ] found that topical urea is able to encourage corneal re-epithelialization and to limit epithelial damage after injury to corneal epithelium. Therefore, all the beforehand mentioned studies about the ophthalmic use of HA and urea suggest that HA cross-linked with urea [ 31 ] could be an innovative promising ingredient for eye drops to induce corneal re-epithelialization.…”
Section: Introductionmentioning
confidence: 99%